2014
DOI: 10.2174/1871520614666140611101040
|View full text |Cite
|
Sign up to set email alerts
|

Paris polyphylla: Chemical and Biological Prospectives

Abstract: Paris polyphylla J.E. Smith is extensively used in traditional systems of Indian and Chinese medicines mainly for its anticancerous property. The national and international demand for P. polyphylla is constantly increasing and most of the supplies come from wild. Illegal and unscientific exploitation coupled with habitat destruction decreases the natural population of the herb, as a consequence this species comes under vulnerable category. Restoration and conservation of the natural population of this potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…The chemical composition of Chonglou includes steroidal saponins, phytoecdysones, phytosterols, flavonoids and fatty acid esters considered as the main constituents of Rhizoma paridis (Negi et al, ; Wang et al, ; Wu, Zhang, Xu, Wang, & Zhang, ). Among them, steroidal saponins are used as characteristic compounds for quality control (National Pharmacopoeia Committee, ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of Chonglou includes steroidal saponins, phytoecdysones, phytosterols, flavonoids and fatty acid esters considered as the main constituents of Rhizoma paridis (Negi et al, ; Wang et al, ; Wu, Zhang, Xu, Wang, & Zhang, ). Among them, steroidal saponins are used as characteristic compounds for quality control (National Pharmacopoeia Committee, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the CYP90B subfamily has been well known to catalyze the rate-limiting sterol C22hydroxylation in brassinosteroid (BR) biosynthetic pathway 23,24 ; and it also displays low activity of sterol 16-hydroxylation 25 . Since the contents of pennogenin-derived saponins are low in the storage tissue rhizome throughout different living stages ( Supplementary Table 10) with diosgenin-based saponins being the main components 26 , we could not exclude the possibility that pennogenin might be a "side-product" that is generated by a moonlight P450 activity during the production of diosgenin.…”
Section: Biochemical Confirmation Of This Hypothesis Is Currently Undmentioning
confidence: 99%
“…Studies have shown that PR has diverse pharmacological effects including antitumor [11][12][13], antimicrobial [14], anthelmintic activities [15], promoting hemostasis [16], antifungal [17], and immuno-stimulating properties [18]. The major active components in PR are spirostanol saponins including polyphyllin VII, VI, I, II, which are as the markers for quality control of PR [19]. Besides the spirostanol glycosides, furostanol glycosides with an open side-chain at C-22 is another type of steroidal saponins in PR [20].…”
Section: Introductionmentioning
confidence: 99%